Hallucinations - Sacks, Oliver, 1933-2015 (Alfred A. Knopf, 2012)
An investigation into the types, physiological sources, and cultural resonances of hallucinations traces everything from the disorientations of sleep and intoxication to the manifestations of injury and illness.